An Academic 'Glass Cliff'? Exploring the Increase of Women in Swedish Higher Education Management - Helen Peterson (Athens Institute for Education and Research, 2014)
Sweden has the highest percentage of female university Vice Chancellors in Europe. Some of the factors that have promoted women's representation in senior management in Swedish academia are: political pressure in the form of goals and policies, quantitative target agreements concerning women's representation, top level commitment to gender equality goals, and a network encouraging and supporting aspiring women managers. However, although women appear to break the glass ceiling, this paper sets out to investigate whether women are genuinely empowered in Swedish academia. Drawing on qualitative semi-structured interviews with 22 senior managers in Swedish higher education, the paper reveals some of the challenges facing manager-academics: increasing workload, role conflict and decreasing status and prestige. Situating women's increase in higher education management in a setting permeated by these challenges stimulates an analysis using theories about feminization of occupations and the metaphor 'glass cliff'. Feminization refers to how women's increase in an occupation often occurs simultaneously as it is transformed into a less prestigious work, with limited opportunities for advancement and weakened job security. The related concept 'glass cliff' describes a phenomenon when women are more likely to be appointed to precarious leadership roles in situations of turbulence and problematic organizational circumstances. The paper argues that women have been allowed to enter into management positions in higher education at the same time as these positions decline in status, merit and prestige and become more time-consuming and harder to combine with a successful scholarly career. Women are thus placed on an academic glass cliff. Keywords: Higher Education, management, women.